1999
DOI: 10.1111/j.1095-8312.1999.tb01925.x
|View full text |Cite
|
Sign up to set email alerts
|

Origin of the Sulawesi macaques (Cercopithecidae: Macaca) as suggested by mitochondrial DNA phylogeny

Abstract: One of the sharpest biogeographical transitions in the world occurs between the Indonesian islands of Borneo and Sulawesi; this transition is demarcated by Wallace's line. Macaque monkeys represent an interesting anomaly to faunal distributions in this region as they occur on both sides of Wallace's line, with Macaca fmcicularis, M. nemestrina and other species to the west and seven Sulawesi species to the east. We have investigated macaque evolution and dispersal in the Sunda region and Sulawesi using phyloge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
73
0
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(80 citation statements)
references
References 38 publications
6
73
0
1
Order By: Relevance
“…For these reasons, we also suspect that paraphyly of Sulawesi macaque mtDNA reported by Evans et al (1999) based on data from another region of the mtDNA is better attributed to homoplasy, as has been suggested (Deinard and Glen Smith 2001), than to recombination.…”
Section: Tablementioning
confidence: 85%
See 2 more Smart Citations
“…For these reasons, we also suspect that paraphyly of Sulawesi macaque mtDNA reported by Evans et al (1999) based on data from another region of the mtDNA is better attributed to homoplasy, as has been suggested (Deinard and Glen Smith 2001), than to recombination.…”
Section: Tablementioning
confidence: 85%
“…: A signal of recombination was detected in mtDNA of papionin monkeys (Piganeau et al 2004;Tsaousis et al 2005), including M. nemestrina (R. Setyadji, B. Suryobroto, T. Watanabe, and O. Takenaka, unpublished data; Evans et al 1999), Sulawesi macaques (Evans et al 1999), baboons (Newman et al 2004), and mandrills (Telfer et al 2003). After correction for multiple tests, one of four indirect tests for recombination used by Piganeau et al (2004) support recombination in the mtDNA data in this study from Borneo M. nemestrina (probability of the null hypothesis of no recombination (P no recomb ) ¼ 0.216, 0.015, 0.768, and .0.001 according to LDr 2 , LDD9, geneconv, and Max x 2 statistic tests).…”
Section: Tablementioning
confidence: 99%
See 1 more Smart Citation
“…However, our work on Chitaura grasshoppers in Sulawesi (Walton et al 1997;Bridle et al 2001) used divergence in different types of markers-morphology, color patterns, and mtDNA to locate the positions of two contact zones in northern Sulawesi, and compare their positions with those of macaques given by Evans et al (1999). These data revealed that, in contrast to the conclusion stated by Evans et al (2003;p.…”
mentioning
confidence: 85%
“…This has been modeled by Irwin (2002) who showed that the sampling of such a marker can lead to erroneous inferences of past fragmentation. To avoid such artifacts, it is important to survey multiple marker loci or to examine concordance between genetic and phenotypic variation, as Evans et al (1999Evans et al ( , 2001) have done in their previous studies of macaques.…”
mentioning
confidence: 99%